The Acute-Phase Proteins Serum Amyloid A and C Reactive Protein in Transudates and Exudates - Alessandra M. Okino; Cristiani Bürger; Jefferson R. Cardoso; Edson L. Lavado; Paulo A. Lotufo; Ana Campa (Mediators of Inflammation)
The distinction between exudates and transudates is very important in the patient management. Here we evaluate whether the acute-phase protein serum amyloid A (SAA), in comparison with C reactive protein (CRP) and total protein (TP), can be useful in this discrimination. CRP, SAA, and TP were determined in 36 exudate samples (27 pleural and 9 ascitic) and in 12 transudates (9 pleural and 3 ascitic). CRP, SAA, and TP were measured. SAA present in the exudate corresponded to 10%